Efficient finance regulator as supporter for financial stability of inhabitants - Vanaga, Rita; Sloka, Biruta (University of Latvia, 2020)
Recent developments in banking sector in Latvia especially related with PNB Bank where bank accounts of many retired people were located leads to requirements for proficiency of Finance Regulator which has to be efficiently financed, stable and professional. In different countries Finance Regulators have different models of their financing. Aim of the study is to investigate different approaches for Finance Regulator financing and analyse expert views on possible development of Finance Regulator financing model in Latvia. Research methods applied: scientific publications and previous conducted research results analysis and expert survey for possible financing model changes in Latvia. In expert survey for analysis of expert views in many cases it was used evaluation scale 1-10 to better analyse expert views. For analysis of expert views it was used indicators of descriptive statistics, cross-tabulations and factor analysis. Research results indicated that Latvia has a great challenge for best possible model of Finance Regulator financing as the current financing model causes problems as currently Finance Regulator is financed by existing finance institutions which Finance Regulator has to monitor.
Keywords: account location for retired people; financial literacy; finance regulator; finance system stability; Research Subject Categories::SOCIAL SCIENCES::Business and economics